IMPLEMENTATION OF JIBRIL METHOD IN INCREASING THE ABILITY TO READ THE KORAN CLASS C 2 TAKHASSUSUL KORAN INSTITUTIONS OF DARUL HIKMAH - Mufaizin; Bahrul Ulum (Fakultas Tarbiyah, Universitas Ibrahimy, 2020)
This research is a Classroom Action Research (CAR), which is research based onproblems that arise in the learning process. The basis of this class action research departs from the beginning of the study of learning the Koran in class, the results are discussed with the homeroom teacher, class and group of teachers to diagnose the situation in the classroom, then planned, and systematically reflect with various alternative actions to overcome the problems of students in order to improve and enhance the ability to read the Koran. While the purpose of this study is intended: first to find out whether the method of Jibril is an appropriate learning method in improving the ability to read Al Koran for students of takhassusul koran Darul Hikmah. And secondly, to find out whether the method of Jibril can improve the ability to read Al-Koran students tahsin children takhassusul koran institute Darul Hikmah. From this research it can be seen that the Jibril method is an appropriate learning method in improving the ability to read the Koran tahsin students children takhassusul koran institute darul hikmah, the Jibril method can improve the reading ability of the Koran tahsin students children of the superstitious koran darul hikmah.